Reassessing the basal detachment of the Ungava Orogen, northern Québec: New insights from petrochronology - Isabelle Therriault; Kyle P. Larson; Mehdi Jouhari; Carl Guilmette; Marc-Antoine Vanier (Precambrian Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Corrigendum to “Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales” [Environ. Res. (2026) 124912] - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David C. Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Genetic and ecological evidence for cryptic divergence within a species complex of rockfish in the Eastern Pacific - Anita Wray; R. N. Lou; G. Longo; W. Larson; P. H. Sudmant; J. Benante; J. H. Harms; J. R. Hyde; K. M. Nichols (Conservation Genetics, 2026)

The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Integrated Reanalysis of Global Riverine Fish eDNA Datasets Shows Robustness and Congruence of Biodiversity Conclusions - Yan Zhang; Heng Zhang; Hiroshi Akashi; Camille P. Albouy; Kara J. Andres; José Barquín; Jeanine Brantschen; Richard E. Connon; Joseph M. Craine; Deirdre Gleeson; Alejandra Goldenberg‐Vilar; Alexia M. González‐Ferreras; et al. (Molecular Ecology, 2026)
The analysis of environmental DNA (eDNA) has revolutionized biodiversity assessments in aquatic ecosystems, enabling non‐invasive monitoring of fish communities across diverse regions. However, the global comparability of these eDNA datasets remains ambiguous due to heterogeneous sampling protocols and bioinformatic workflows across studies, making it difficult to assess how robust and comparable the biodiversity patterns inferred from these datasets actually are. Here, we conducted a meta‐analysis of 58 riverine fish eDNA metabarcoding studies, covering 1818 sampling sites worldwide, to evaluate the robustness of eDNA‐derived biodiversity patterns. We found that species richness estimates and metrics of community structure derived under a common bioinformatic workflow were overall consistent with those of original analyses, despite the relatively high variability in bioinformatic analyses in the respective original studies. Contrastingly, congruence of species identity varied more extensively across datasets, mostly reflecting different completeness and regional relevance of reference databases. Restricting taxonomic assignment to basin‐specific species pools improved species identification accuracy, while datasets lacking publicly accessible or well‐curated reference data were more prone to mismatches. Year of sampling had a positive effect on taxonomic congruence, such that more recent studies showed increased robustness, also reflecting improved reference database coverage and enhanced species‐level identification over time and overall method congruence in more recent years. Overall, the suitability and potential of eDNA for global biodiversity monitoring is corroborating overall robust biodiversity estimates, irrespective of the bioinformatic approaches. Our study underlines the effectiveness and need for further harmonization of bioinformatic workflows and strengthened region‐specific reference databases for improved taxonomic resolution and comparability across studies.

Investigating the generation of transport-parallel gradients in ductile strain and kinematic vorticity in the footwalls of metamorphic core complexes: Insights from the Northern Snake Range, Nevada, USA - Aurora E. Rosenberger; Sean P. Long; Nolan Blackford; Johannes Haemmerli; Kyle P. Larson; Brianna Dowler; Scott Jess (Journal of Structural Geology, 2026)

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

COMBINA: coastal ocean marine biosecurity international network of the Americas - Gregory M. Ruiz; Antonio Brante; James T. Carlton; Amy L. Freestone; Inti Keith; Brenda M. Soler-Figueroa; Mark E. Torchin; Alejandro Bortolus; Ricardo Coutinho; Maria Cecilia Trindade de Castro; Thomas Wayne Therriault; Sergio Andrés Benavides Avendaño; et al. (Biological Invasions, 2025)

MLH1 c.27G>A (p.Arg9=) is a synonymous likely/pathogenic variant underlying variably mosaic constitutional MLH1 methylation in Lynch syndrome - Rocio Alvarez; Paula Climent-Cantó; GiWon Shin; Francesca Paola Aguirre; Lisa Zhou; Dennis J. Hazelett; Brent K. Larson; Covadonga Vara; Gabriel Capellá; Víctor Lorca Castellanos; Pilar Garre Rubio; Françoise Desseigne; et al. (Familial Cancer, 2025)

Environmental DNA reveals the Salamander Mussel Simpsonaias ambigua alive in Illinois, USA , after a century in obscurity - Sarah A. Douglass; Savanna Palmer; Ashleigh R. McCallum; Olivia P. Reves; Hayley A. Robinson; Allison J. Rutledge; Jordan H. Hartman; Eric R. Larson; Mark A. Davis (Ecology, 2025)

SRM survey and membership shifts demonstrate “change on the range” - Jamie Dahl; Julie E. Larson; Cameron Duquette; María E. Fernández-Giménez; Evan P. Tanner; Devii Rao; Gene Gloeckner (Rangelands, 2025)

Oral anti-endotoxin immunoglobulin Y (IgY) does not impact gut microbiome development in the first 28 days in foals - M. Mork; M.B. Conrad; A.M. Trauner; J. Hull; M. Hawkins; B. Robley; P. Larson; N. Pinkham; T. Wolfe; Q. Wang; S. Walk; A.N. Bradbery (Journal of Equine Veterinary Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Americans’ support for climate justice - Jennifer P. Carman; Danning Lu; Matthew Ballew; Joshua Low; Marija Verner; Seth A. Rosenthal; Kristin Barendregt-Ludwig; Gerald Torres; Michel Gelobter; Kate McKenney; Irene Burga; Mark Magaña; et al. (Environmental Science & Policy, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Integration of white mica in situ 87Rb/87Sr with in situ and step-heat 40Ar/39Ar dates in orogenic settings - Dawn A. Kellett; Kyle P. Larson; Diane R. Skipton (Lithos, 2024)

Pollen effects in a changing climate: Ragweed pollen exposure and sleepiness in immunotherapy patients of a Southeastern Michigan allergy clinic - Peter S. Larson; Allison L. Steiner; Erica Bennion; Alan P. Baptist; Marie S. O’Neill; Carina J. Gronlund (International Journal of Biometeorology, 2024)

Structure of dense plumes from a finite-height cylinder in laminar crossflow - Aaron C. True; Lars T. Larson; Anna K. Pauls; John P. Crimaldi (Environmental Fluid Mechanics, 2024)

Defining shear zone deformation and alteration gradients: Pocologan Kennebecasis shear zone, Canadian Appalachians - Nicolas Piette-Lauzière; Kyle P. Larson; Dawn A. Kellett; Rüdiger Kilian; Michael Stipp; Riccardo Graziani; Isabelle Therriault (Tectonophysics, 2024)

Wilder rangelands as a natural climate opportunity: Linking climate action to biodiversity conservation and social transformation - Lavhelesani D. Simba; Mariska te Beest; Heidi-Jayne Hawkins; Keith W. Larson; Anthony R. Palmer; Camilla Sandström; Kathleen G. Smart; Graham I. H. Kerley; Joris P. G. M. Cromsigt (Ambio, 2024)
Rangelands face threats from climate and land-use change, including inappropriate climate change mitigation initiatives such as tree planting in grassy ecosystems. The marginalization and impoverishment of rangeland communities and their indigenous knowledge systems, and the loss of biodiversity and ecosystem services, are additional major challenges. To address these issues, we propose the wilder rangelands integrated framework, co-developed by South African and European scientists from diverse disciplines, as an opportunity to address the climate, livelihood, and biodiversity challenges in the world’s rangelands. More specifically, we present a Theory of Change to guide the design, monitoring, and evaluation of wilder rangelands. Through this, we aim to promote rangeland restoration, where local communities collaborate with regional and international actors to co-create new rangeland use models that simultaneously mitigate the impacts of climate change, restore biodiversity, and improve both ecosystem functioning and livelihoods.

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

Syn-exhumation metasomatic glaucophane-phengite-quartz veins formed at moderate pressures: exploring the control of fO2 and bulk composition on nominally HP metamorphic assemblages - T. A. Ducharme; D. A. Schneider; B. Grasemann; M. Bukała; A. Camacho; K. P. Larson; K. Soukis (Contributions to Mineralogy and Petrology, 2024)

What happens to trees and soils during five decades of experimental nitrogen loading? - P. Högberg; R.W. Lucas; M.N. Högberg; U. Skyllberg; G. Egnell; J. Larson; D. Binkley (Forest Ecology and Management, 2024)

Pseudotachylytes in felsic lower-crustal rocks of the Calabrian Serre massif: A record of deep- or shallow-crustal earthquakes? - Simone Papa; Giorgio Pennacchioni; Alfredo Camacho; Kyle P. Larson (Lithos, 2023)

Coastal response to global warming during the Paleocene-Eocene Thermal Maximum - Glenn R. Sharman; Jacob A. Covault; Peter P. Flaig; Regan Dunn; Preston Fussee-Durham; Toti E. Larson; Timothy M. Shanahan; Kalli Dubois; John B. Shaw; James L. Crowley; Barry Shaulis (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Sound Level Changes the Auditory Cortical Activation Detected with Functional Near-Infrared Spectroscopy - Sterling W. Sheffield; Eric Larson; Iliza M. Butera; Andrea DeFreese; Baxter P. Rogers; Mark T. Wallace; G. Christopher Stecker; Adrian K. C. Lee; Rene H. Gifford (Brain Topography, 2023)

Sex differences in neuroendocrine, sympathetic nervous system, and affect responses to acute stress in cannabis users - Eric R. Larson; Alexandra B. Moussa-Tooks; Rachel L. Tullar; Amanda R. Bolbecker; Brian F. O’Donnell; William P. Hetrick; Krista M. Wisner (Psychopharmacology, 2023)

Metasomatic origin of the Himalayan banded tourmaline leucogranite - Brendan Dyck; Kyle P. Larson (Contributions to Mineralogy and Petrology, 2023)

Acrylic acid and DMSP lyases in the green algae Ulva - Giovanna Pesante; Edith Forestier; Swen Langer; Andrew Danby; John Angus; Mark Gronnow; Joseph P. Bennett; Tony R. Larson; Thierry Tonon (Algal Research, 2023)

Examining the Octopus joubini species complex (Cephalopoda: Octopodidae) in the northeastern Gulf of Mexico - H. Holloway; P. Larson; J. S. Doody; H. Judkins (Marine Biodiversity, 2023)

Far from boring: A new Grenvillian perspective on Mesoproterozoic tectonics - Félix Gervais; Alexandre Beaudry; Charles Kavanagh-Lepage; Abdelali Moukhsil; Kyle P. Larson; Carl Guilmette (Earth and Planetary Science Letters, 2023)

A comparison of 87Rb/87Sr and 40Ar/39Ar dates: Evaluating the problem of excess 40Ar in Himalayan mica - Kyle P. Larson; Mark Button; Sudip Shrestha; Alfredo Camacho (Earth and Planetary Science Letters, 2023)

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Tree Mortality may Drive Landscape Formation: Comparative Study from Ten Temperate Forests - P. Šamonil; P. Daněk; J. A. Lutz; K. J. Anderson-Teixeira; J. Jaroš; J. D. Phillips; A. Rousová; D. Adam; A. J. Larson; J. Kašpar; D. Janik; I. Vašíčková; et al. (Ecosystems, 2023)

Geochemistry and in-situ U-Th/Pb Geochronology of the Jambil Meta-Carbonatites, Northern Pakistan: Implications on Petrogenesis and Tectonic Evolution - Asad Khan; Shah Faisal; Kyle P. Larson; Delores M. Robinson; Huan Li; Zaheen Ullah; Mark Button; Javed Nawab; Muhammad Farhan; Liaqat Ali; Muhammad Ali (Journal of Earth Science, 2023)

Riverine drift communities during larval fish dispersal over multiple recruitment years - Joseph P. Receveur; Alberto Doretto; Edward A. Baker; Douglas L. Larson; John M. Bauman; Ryan Walquist; M. Eric Benbow; Kim T. Scribner (Hydrobiologia, 2022)

Miocene anatexis, cooling and exhumation in the Khumbu Himal, Nepal - Kyle P. Larson; John M. Cottle; Alfredo Camacho; Stephen Piercey; Djordje Grujic (International Geology Review, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Progressive development of E-W extension across the Tibetan plateau: A case study of the Thakkhola graben, west-central Nepal - Alex D. Brubacher; Kyle P. Larson; John M. Cottle; William Matthews; Alfredo Camacho (International Geology Review, 2021)

Asymmetry of marine invasions across tropical oceans - Mark E. Torchin; Amy L. Freestone; Linda McCann; Kristen Larson; Carmen SchlÖder; Brian P. Steves; Paul Fofonoff; Michele F. Repetto; Gregory M. Ruiz (Ecology, 2021)
Understanding the mechanisms of spatial variation of biological invasions, across local‐to‐global scales, has been a major challenge. The importance of evolutionary history for invasion dynamics was noted by Darwin, and several studies have since considered how biodiversity of source and recipient regions can influence the probability of invasions. For over a century, the Panama Canal has connected water bodies and biotas with different evolutionary histories, and created a global shipping hot spot, providing unique opportunities to test mechanisms that affect invasion patterns. Here, we test for asymmetry in both the extent of invasions and predation effects, a possible mechanism of biotic resistance, between two tropical oceans at similar latitudes. We estimated nonnative species (NNS) richness for sessile marine invertebrates, using standardized field surveys and literature synthesis, to examine whether invasions are asymmetrical, with more NNS present in the less diverse Pacific compared to the Atlantic. We also experimentally tested whether predation differentially limits the abundance and distribution of these invertebrates between oceans. In standardized surveys, observed total NNS richness was higher in the Pacific (18 NNS, 30% of all Pacific species) than the Atlantic (11 NNS, 13% of all Atlantic species). Similarly, literature‐based records also display this asymmetry between coasts. When considering only the reciprocal exchange of NNS between Atlantic and Pacific biotas, NNS exchange from Atlantic to Pacific was eightfold higher than the opposite direction, exceeding the asymmetry predicted by random exchange based simply on differences of overall diversity per region. Predation substantially reduced biomass and changed NNS composition in the Pacific, but no such effects were detected on the Atlantic coast. Specifically, some dominant NNS were particularly susceptible to predation in the Pacific, supporting the hypothesis that predation may reduce the abundance of certain NNS here. These results are consistent with predictions that high diversity in source regions, and species interactions in recipient regions, shape marine invasion patterns. Our comparisons and experiments across two tropical ocean basins, suggest that global invasion dynamics are likely driven by both ecological and evolutionary factors that shape susceptibility to and directionality of invasions across biogeographic scales.

Molecular Markers of Biogenic and Oil-Derived Hydrocarbons in Deep-Sea Sediments Following the Deepwater Horizon Spill - Isabel C. Romero; Jeffrey P. Chanton; Gregg R. Brooks; Samantha Bosman; Rebekka A. Larson; Austin Harris; Patrick Schwing; Arne Diercks (Frontiers in Marine Science, 2021)
Following the Deepwater Horizon oil spill (DWHOS), the formation of an unexpected and extended sedimentation event of oil-associated marine snow (MOSSFA: Marine Oil Snow Sedimentation and Flocculent Accumulation) demonstrated the importance of biology on the fate of contaminants in the oceans. We used a wide range of compound-specific data (aliphatics, hopanes, steranes, triaromatic steroids, polycyclic aromatics) to chemically characterize the MOSSFA event containing abundant and multiple hydrocarbon sources (e.g., oil residues and phytoplankton). Sediment samples were collected in 2010–2011 (ERMA-NRDA programs: Environmental Response Management Application – Natural Resource Damage Assessment) and 2018 (REDIRECT project: Resuspension, Redistribution and Deposition of Deepwater Horizon recalcitrant hydrocarbons to offshore depocenter) in the northern Gulf of Mexico to assess the role of biogenic and chemical processes on the fate of oil residues in sediments. The chemical data revealed the deposition of the different hydrocarbon mixtures observed in the water column during the DWHOS (e.g., oil slicks, submerged-plumes), defining the chemical signature of MOSSFA relative to where it originated in the water column and its fate in deep-sea sediments. MOSSFA from surface waters covered 90% of the deep-sea area studied and deposited 32% of the total oil residues observed in deep-sea areas after the DWHOS while MOSSFA originated at depth from the submerged plumes covered only 9% of the deep-sea area studied and was responsible for 15% of the total deposition of oil residues. In contrast, MOSSFA originated at depth from the water column covered only 1% of the deep-sea area studied (mostly in close proximity of the DWH wellhead) but was responsible for 53% of the total deposition of oil residues observed after the spill in this area. This study describes, for the first time, a multi-chemical method for the identification of biogenic and oil-derived inputs to deep-sea sediments, critical for improving our understanding of carbon inputs and storage at depth in open ocean systems.

Resuspension, Redistribution, and Deposition of Oil-Residues to Offshore Depocenters After the Deepwater Horizon Oil Spill - Arne R. Diercks; Isabel C. Romero; Rebekka A. Larson; Patrick Schwing; Austin Harris; Samantha Bosman; Jeffrey P. Chanton; Gregg Brooks (Frontiers in Marine Science, 2021)
The focus of this study was to determine the long-term fate of oil-residues from the 2010 Deepwater Horizon (DwH) oil spill due to remobilization, transport, and re-distribution of oil residue contaminated sediments to down-slope depocenters following initial deposition on the seafloor. We characterized hydrocarbon residues, bulk sediment organic matter, ease of resuspension, sedimentology, and accumulation rates to define distribution patterns in a 14,300 km 2 area southeast of the DwH wellhead (1,500 to 2,600 m water depth). Oil-residues from the DwH were detected at low concentrations in 62% of the studied sites at specific sediment layers, denoting episodic deposition of oil-residues during 2010–2014 and 2015–2018 periods. DwH oil residues exhibited a spatial distribution pattern that did not correspond with the distribution of the surface oil slick, subsurface plume or original seafloor spatial expression. Three different regions were apparent in the overall study area and distinguished by the episodic nature of sediment accumulation, the ease of sediment resuspension, the timing of oil-residue deposition, carbon content and isotopic composition and foram fracturing extent. These data indicate that resuspension and down-slope redistribution of oil-residues occurred in the years following the DwH event and must be considered in determining the fate of the spilled oil deposited on the seafloor.

Fine-Scale Air Pollution Models for Epidemiologic Research: Insights From Approaches Developed in the Multi-ethnic Study of Atherosclerosis and Air Pollution (MESA Air) - Kipruto Kirwa; Adam A. Szpiro; Lianne Sheppard; Paul D. Sampson; Meng Wang; Joshua P. Keller; Michael T. Young; Sun-Young Kim; Timothy V. Larson; Joel D. Kaufman (Current Environmental Health Reports, 2021)

The FamilyTalk randomized controlled trial: patient-reported outcomes in clinical genetic sequencing for colorectal cancer - Sukh Makhnoon; Deborah J. Bowen; Brian H. Shirts; Stephanie M. Fullerton; Eric B. Larson; James D. Ralston; Kathleen A. Leppig; David R. Crosslin; David Veenstra; Gail P. Jarvik (Cancer Causes & Control, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Caveolin-1 regulates medium spiny neuron structural and functional plasticity - Katherine R. Tonn Eisinger; Andrew D. Chapp; Samuel P. Swanson; Daniel Tam; Natalie M. Lopresti; Erin B. Larson; Mark J. Thomas; Lorene M. Lanier; Paul G. Mermelstein (Psychopharmacology, 2020)

Challenges in the Measurement and Interpretation of Serum Titanium Concentrations - Jie J. Yao; Eric A. Lewallen; Roman Thaler; Amel Dudakovic; Michelle Wermers; Patrick Day; Steve Eckdahl; Paul Jannetto; Joshua A. Bornhorst; A. Noelle Larson; Matthew P. Abdel; David G. Lewallen; et al. (Biological Trace Element Research, 2020)

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

“It would be so much easier”: health system-led genetic risk notification—feasibility and acceptability of cascade screening in an integrated system - Nora B. Henrikson; Paula R. Blasi; Stephanie M. Fullerton; Jane Grafton; Kathleen A. Leppig; Gail P. Jarvik; Eric B. Larson (Journal of Community Genetics, 2019)

Effects of optical sensing based variable rate nitrogen management on yields, nitrogen use and profitability for cotton - M. Stefanini; J. A. Larson; D. M. Lambert; X. Yin; C. N. Boyer; P. Scharf; B. S. Tubaña; J. J. Varco; D. Dunn; H. J. Savoy; M. J. Buschermohle (Precision Agriculture, 2019)

Cervical Cancer Patients’ Willingness and Ability to Serve as Health Care Educators to Advocate for Human Papillomavirus Vaccine Uptake - Ilene G. Ladd; Radhika P. Gogoi; Tyler L. Bogaczyk; Sharon L. Larson (Journal of Cancer Education, 2019)

Linking preconditioning to extreme ENSO events and reduced ensemble spread - Sarah M. Larson; Ben P. Kirtman (Climate Dynamics, 2019)

Future Directions in Sea Otter Research and Management - Randall W. Davis; James L. Bodkin; Heather A. Coletti; Daniel H. Monson; Shawn E. Larson; Lilian P. Carswell; Linda M. Nichol (Frontiers in Marine Science, 2019)

Factors Affecting Disaster Preparedness, Response, and Recovery Using the Community Capitals Framework - Amber Himes-Cornell; Carlos Ormond; Kristin Hoelting; Natalie C. Ban; J. Zachary Koehn; Edward H. Allison; Eric C. Larson; Daniel H. Monson; Henry P. Huntington; Thomas A. Okey (Coastal Management, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Environmental DNA (eDNA) detects the invasive crayfishes Orconectes rusticus and Pacifastacus leniusculus in large lakes of North America - Eric R. Larson; Mark A. Renshaw; Crysta A. Gantz; John Umek; Sudeep Chandra; David M. Lodge; Scott P. Egan (Hydrobiologia, 2017)

Anthopleura and the phylogeny of Actinioidea (Cnidaria: Anthozoa: Actiniaria) - M. Daly; L. M. Crowley; P. Larson; E. Rodríguez; E. Heestand Saucier; D. G. Fautin (Organisms Diversity & Evolution, 2017)

Drivers of coupled model ENSO error dynamics and the spring predictability barrier - Sarah M. Larson; Ben P. Kirtman (Climate Dynamics, 2017)

Erratum to: Brief exposure to Pope Francis heightens moral beliefs about climate change - Jonathon P. Schuldt; Adam R. Pearson; Rainer Romero-Canyas; Dylan Larson-Konar (Climatic Change, 2017)

Brief exposure to Pope Francis heightens moral beliefs about climate change - Jonathon P. Schuldt; Adam R. Pearson; Rainer Romero-Canyas; Dylan Larson-Konar (Climatic Change, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Do key dimensions of seed and seedling functional trait variation capture variation in recruitment probability? - Julie E. Larson; Roger L. Sheley; Stuart P. Hardegree; Paul S. Doescher; Jeremy J. James (Oecologia, 2016)

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

Effects of age on arterial stiffness and central blood pressure after an acute bout of resistance exercise - Robert S. Thiebaud; Christopher A. Fahs; Lindy M. Rossow; Jeremy P. Loenneke; Daeyeol Kim; J. Grant Mouser; Travis W. Beck; Debra A. Bemben; Rebecca D. Larson; Michael G. Bemben (European Journal of Applied Physiology, 2016)

Participation in cognitively-stimulating activities is associated with brain structure and cognitive function in preclinical Alzheimer’s disease - Stephanie A. Schultz; Jordan Larson; Jennifer Oh; Rebecca Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; Sterling C. Johnson; et al. (Brain Imaging and Behavior, 2015)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Extrusion vs. duplexing models of Himalayan mountain building 3: duplexing dominates from the Oligocene to Present - Dian He; A. Alexander G. Webb; Kyle P. Larson; Aaron J. Martin; Axel K. Schmitt (International Geology Review, 2015)

Can mercury in fish be reduced by water level management? Evaluating the effects of water level fluctuation on mercury accumulation in yellow perch (Perca flavescens) - James H. Larson; Ryan P. Maki; Brent C. Knights; Brian R. Gray (Ecotoxicology, 2014)

Genetic diversity and population structure of sickleweed (Falcaria vulgaris; Apiaceae) in the upper Midwest USA - Sarbottam Piya; Madhav P. Nepal; Jack L. Butler; Gary E. Larson; Achal Neupane (Biological Invasions, 2014)

A flexible spatio-temporal model for air pollution with spatial and spatio-temporal covariates - Johan Lindström; Adam A. Szpiro; Paul D. Sampson; Assaf P. Oron; Mark Richards; Tim V. Larson; Lianne Sheppard (Environmental and Ecological Statistics, 2014)

Persistence and stability of Eastern Afromontane forests: evidence from brevicipitid frogs - Simon P. Loader; F. Sara Ceccarelli; Michele Menegon; Kim M. Howell; Roman Kassahun; Abebe A. Mengistu; Samy A. Saber; Fikirte Gebresenbet; Rafael de Sá; Tim R. B. Davenport; Joanna G. Larson; Hendrik Müller; et al. (Journal of Biogeography, 2014)
Aim The persistence and stability of habitats through time are considered predictors of high levels of biodiversity in some environments. Long‐term habitat persistence and stability may explain the species‐rich, endemic forest fauna and flora of the Eastern Afromontane Biodiversity Region ( EABR ). Using complementary phylogenetic and biogeographical approaches, we examine evolutionary patterns in EABR brevicipitid frogs. Using these data, we test whether brevicipitid history reflects patterns of long‐term forest persistence and/or stability across the EABR . Location East Africa. Methods A dated phylogeny for brevicipitids was constructed using two nuclear and three mitochondrial markers. Alternative diversification models were used to determine signal for constant or varying net diversification rates. Using our dated tree, we identified areas of high phylogenetic diversity ( PD ), and inferred ancestral areas using likelihood and Bayesian approaches. Results Brevicipitids have a long history, with generic diversification among extant lineages pre‐dating the Oligocene (> 33 Ma). Ancestral‐area reconstructions indicate the presence of brevicipitids in the EABR since the Oligocene, and support a scenario of palaeoendemics surviving in EABR refugia. Ancestral‐area reconstructions indicate that the central Eastern Arc Mountains ( EAM ) formed the initial centre of diversification of forest brevicipitids. Measures of PD show that diversity varies across the EABR but is highest in the EAM . Constant net diversification rate in brevicipitids is a significantly better fit than alternative, rate‐variable models. Main conclusions The degree of persistence of forest habitats appears to be a contributing factor to the varying levels of diversity across the EABR in brevicipitids (and other organisms). In contrast to the Southern Highlands and Ethiopian Bale Mountains, the EAM stands out as an area that enabled the constant accumulation of brevicipitid species over a long period of time.

Convergent Surface Water Distributions in U.S. Cities - M. K. Steele; J. B. Heffernan; N. Bettez; J. Cavender-Bares; P. M. Groffman; J. M. Grove; S. Hall; S. E. Hobbie; K. Larson; J. L. Morse; C. Neill; K. C. Nelson; et al. (Ecosystems, 2014)

Distribution and dietary regulation of an associated facultative Rhizobiales-related bacterium in the omnivorous giant tropical ant, Paraponera clavata - Hannah K. Larson; Shana K. Goffredi; Erica L. Parra; Orlando Vargas; Adrián A. Pinto-Tomas; Terrence P. McGlynn (The Science of Nature, 2014)

Development and application of genomic tools to the restoration of green abalone in southern California - K. M. Gruenthal; D. A. Witting; T. Ford; M. J. Neuman; J. P. Williams; D. J. Pondella; A. Bird; N. Caruso; J. R. Hyde; L. W. Seeb; W. A. Larson (Conservation Genetics, 2014)

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

To drink or grasp? How bullet ants (Paraponera clavata) differentiate between sugars and proteins in liquids - Jennifer Jandt; Hannah K. Larson; Peter Tellez; Terrence P. McGlynn (The Science of Nature, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Author reply to Fujimi et al - Richard A. Larson; Ophelia Q. P. Yin (European Journal of Clinical Pharmacology, 2012)

First record of the gobiid fish Aulopareia ocellata (Teleostei: Gobiidae) from Qeshm Island, The Gulf, with discussion of its generic placement - P. Zare; H. K. Larson; A. Toorang (Journal of Fish Biology, 2012)
The poorly known gobiid fish species Aulopareia ocellata is recorded for the first time from the intertidal zone of north‐east Qeshm Island, The Gulf, Iran. The species has been referred to previously as Parachaeturichthys ocellatus , but here is placed in Aulopareia , pending a revision of the genus. The morphological features of A. ocellata are described and compared with congeners and brief comparisons of the genera Aulopareia and Parachaeturichthys are provided. A full description of the species is given, with illustration of the sensory papillae and head‐pore pattern. This species has previously been recorded from India (Mumbai) and Pakistan (Karachi).

An All-Atom Model of the Structure of Human Copper Transporter 1 - Igor F. Tsigelny; Yuriy Sharikov; Jerry P. Greenberg; Mark A. Miller; Valentina L. Kouznetsova; Christopher A. Larson; Stephen B. Howell (Cell Biochemistry and Biophysics, 2012)

Population pharmacokinetic and exposure-response analysis of nilotinib in patients with newly diagnosed Ph+ chronic myeloid leukemia in chronic phase - Richard A. Larson; Ophelia Q. P. Yin; Andreas Hochhaus; Giuseppe Saglio; Richard E. Clark; Hirohisa Nakamae; Neil J. Gallagher; Eren Demirhan; Timothy P. Hughes; Hagop M. Kantarjian; Philipp D. le Coutre (European Journal of Clinical Pharmacology, 2012)

Genetic variants associated with the white blood cell count in 13,923 subjects in the eMERGE Network - David R. Crosslin; Andrew McDavid; Noah Weston; Sarah C. Nelson; Xiuwen Zheng; Eugene Hart; Mariza de Andrade; Iftikhar J. Kullo; Catherine A. McCarty; Kimberly F. Doheny; Elizabeth Pugh; Abel Kho; et al. (Human Genetics, 2012)

What can phylogeographic breaks in the livebearer Poeciliopsis turrubarensis tell about fish community boundaries in western Costa Rica? - A. D. Larson; P. L. Scarborough; C. L. Sayre; J. B. Johnson (Journal of Fish Biology, 2012)
This study asks if the geographic boundary delineating two fish communities in western Costa Rica is congruent with a phylogeographic break in a single widespread fish species Poeciliopsis turrubarensis (Poeciliidae) that spans this area. Such congruence would suggest that a common historical event ( e.g . geological or climatic) could be responsible for both patterns. It was found that there was a shared break across a region in central Costa Rica suggesting a common cause may be responsible for both the abrupt shift in fish community composition and the genetic break in P. turrubarensis .

Exercise economy in African American and European American women - Gary R. Hunter; John P. McCarthy; Marcas M. Bamman; D. Enette Larson-Meyer; Gordon Fisher; Bradley R. Newcomer (European Journal of Applied Physiology, 2011)

Age, muscle fatigue, and walking endurance in pre-menopausal women - Gary R. Hunter; C. Scott Bickel; Pedro Del Corral; Nuala M. Byrne; Andrew P. Hills; D. Enette Larson-Meyer; Marcas M. Bamman; Bradley R. Newcomer (European Journal of Applied Physiology, 2011)

The three-dimensional structure of the FMO protein from Pelodictyon phaeum and the implications for energy transfer - Chadwick R. Larson; Chenda O. Seng; Lisa Lauman; Heather J. Matthies; Jianzhong Wen; Robert E. Blankenship; James P. Allen (Photosynthesis Research, 2011)

The feasibility of low CO2 concentration targets and the role of bio-energy with carbon capture and storage (BECCS) - Christian Azar; Kristian Lindgren; Michael Obersteiner; Keywan Riahi; Detlef P. van Vuuren; K. Michel G. J. den Elzen; Kenneth Möllersten; Eric D. Larson (Climatic Change, 2010)

Gng12 is a novel negative regulator of LPS-induced inflammation in the microglial cell line BV-2 - Kelley C. Larson; Michael P. Draper; Maciej Lipko; Michal Dabrowski (Inflammation Research, 2010)

Structures of proteins and cofactors: X-ray crystallography - J. P. Allen; C. Seng; C. Larson (Photosynthesis Research, 2009)

Gng12 is a novel negative regulator of LPS-induced inflammation in the microglial cell line BV-2 - Kelley C. Larson; Maciej Lipko; Michal Dabrowski; Michael P. Draper (Inflammation Research, 2009)

Combining landslide and contaminant risk: a preliminary assessment - Gunnel I. Göransson; David Bendz; P. Magnus Larson (Journal of Soils and Sediments, 2009)

Localization of myosin-Va in subpopulations of cells in rat endocrine organs - Foued S. Espindola; Silmara R. Banzi; Luciana K. Calabria; Rodrigo J. Custódio; Ricardo A. Oliveira; Leandro D. Procópio; Andreia B. P. Lima; Jair P. Cunha-Junior; Milton V. Coelho; Iêda M. L. Guedes; Cláudia H. Pellizzon; Roy E. Larson; et al. (Cell and Tissue Research, 2008)

Character and significance of spectacular layering features developed in the thin, alkali-basaltic sills of the Ulvö Gabbro Complex, Sweden - S. Å. Larson; K. J. Hogmalm; W. P. Meurer (Mineralogy and Petrology, 2008)

Threshold elemental ratios of carbon and phosphorus in aquatic consumers - Paul C. Frost; Jonathan P. Benstead; Wyatt F. Cross; Helmut Hillebrand; James H. Larson; Marguerite A. Xenopoulos; Takehito Yoshida (Ecology Letters, 2006)
Inadequate supply of one or more mineral elements can slow the growth of animal consumers and alter their physiology, life history and behaviour. A key concept for understanding nutrient deficiency in animals is the threshold elemental ratio (TER), at which growth limitation switches from one element to another. We used a stoichiometric model that coupled animal bioenergetics and body elemental composition to estimate TER of carbon and phosphorus (TER C:P ) for 41 aquatic consumer taxa. We found a wide range in TER C:P (77–3086, ratio by atoms), which was generated by interspecific differences in body C : P ratios and gross growth efficiencies of C. TER C:P also varied among aquatic invertebrates having different feeding strategies, such that detritivores had significantly higher threshold ratios than grazers and predators. The higher TER C:P in detritivores resulted not only from lower gross growth efficiencies of carbon but also reflected lower body P content in these consumers. Supporting previous stoichiometric theory, we found TER C:P to be negatively correlated with the maximum growth rate of invertebrate consumers. By coupling bioenergetics and stoichiometry, this analysis revealed strong linkages among the physiology, ecology and evolution of nutritional demands for animal growth.

Molecular targeting of the lymphovascular system for imaging and therapy - Heiko Schöder; Edwin C. Glass; Alain P. Pecking; Jay K. Harness; Anne M. Wallace; Peter Hirnle; Jean L. Alberini; Didier Vilain; Steven M. Larson; Carl K. Hoh; David R. Vera (Cancer and Metastasis Reviews, 2006)

Inverse relationship between exercise economy and oxidative capacity in muscle - Gary R. Hunter; Marcas M. Bamman; D. Enette Larson-Meyer; Denis R. Joanisse; John P. McCarthy; Tamilane E. Blaudeau; Bradley R. Newcomer (European Journal of Applied Physiology, 2005)

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)

Pharmacokinetics of beclomethasone 17-monopropionate from a beclomethasone dipropionate extrafine aerosol in adults with asthma - Lester I. Harrison; Sarala Kurup; Craig Wagner; Bruce P. Ekholm; Julie S. Larson; Harold B. Kaiser (European Journal of Clinical Pharmacology, 2002)

Effects of Rock Climbing on Populations of Presettlement Eastern White Cedar ( Thuja occidentalis ) on Cliffs of the Niagara Escarpment, Canada - P. E. Kelly; D. W. Larson (Conservation Biology, 1997)
Cliffs of the Niagara Escarpment support a self‐sustaining presettlement forest of eastern white cedar ( Thuja occidentalis L.) in which some trees are over 1000 years old. Many of the cliffs are also popular locations for recreational rock climbing. Our study employed a stratified random sampling design to assess the impact of rock climbing on populations of cliff‐face and cliff‐edge trees. Tree density and age structure were compared between four climbed and three unclimbed sites in the vicinity of Milton, Ontario. Signs of physical damage were also recorded for the trees sampled at each site. The results showed that living tree density on the cliff face was lower in climbed areas. The age structures of these forests showed that the numbers of older and younger age classes have been reduced on climbed cliff faces compared with unclimbed areas. A high percentage of trees on climbed cliff faces showed evidence of damage by humans. These trends were not as apparent on cliff edges where other disturbances have affected age structure. We recommend that cliff faces be explored for the presence of presettlement forest and that recreation managers of lands with exposed cliff faces incorporate rock climbing considerations into their management plans. Monitoring programs would help track levels of disturbance. Education of the climbing community would be the most effective long‐term solution to limiting disturbance in sensitive areas.

Soil moisture relations at the tree/crop interface in black locust alleys - C. K. Ssekabembe; P. R. Henderlong; M. Larson (Agroforestry Systems, 1994)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)